Topsoil Thickness and Its Chemical Properties between Tea Plantation and Bare Land on Different Slopes - Faris Nur Fauzi Athallah; Restu Wulansari (Green Engineering Society, 2025)
Land degradation in Indonesia is often attributed to human activities and high rainfall. The existence of forest land clearing and conversion into non-agricultural land causes topsoil erosion and structural damage, reducing the capacity to hold water and nutrients. The phenomenon contributes to the degradation of tea (Camellia sinensis) plantation, showing the need to improve agricultural land by maintaining soil ecosystems. Therefore, this study aimed to compare soil from tea plantation with bare land on two different slopes based on the chemical quality at Gambung Tea Plantation, Research Institute for Tea and Cinchona. The selected land slope was gentle (0 - 8%) and steep (30 - 40%), producing four environmental combinations. Soil sampling was carried out in two different layers, at 0 - 20 cm and 20 - 40 cm. The experimental parameters observed were topsoil thickness, soil water content, pH, and soil nutrients. The results showed that in steep slope land conditions, tea cover crops maintained topsoil with a thickness of 15.01 cm compared to bare land. This corresponded to topsoil degradation of 19.6% compared to gently slope topographic conditions. In gently slope conditions, both types of land cover did not show significant differences. Tea plant cover maintained better soil water content and reduced soil N loss, although steep slopes showed lower soil nutrient content due to absorption.